Kinematic Selection Criteria in the Search for Resonances - B. B. Levchenko (Advances in High Energy Physics)
In this paper, we discuss some general features of two-body decay kinematics and derive a new set of equations describing boundaries of the physical region in decays. These features via a graphical representation and implementation of selection criteria provide an efficient tool for the background suppression in experimental searches for conventional and exotic (pentaquark, etc.) resonance states.